VD_FINDINFO Plainte / 2024 / 13 vom 23. Mai 2024 - VD Tribunal cantonal (2024)
ÉTAT DES CHARGES, PLAINTELP, COPROPRIÉTÉ, GAGE COLLECTIF, EXTRAIT DU REGISTRE, REGISTRE FONCIER | 641 CC, 798 al. 1 CC, 140 LP, 17 al. 1 LP, 110 al. 1 ORF, 23 ORF, 73e ORFI